Survey Efektivitas Blended Learning pada Materi Pendidikan Jasmani SMA tentang Invasion Games, Net-Games, dan Atletik - Syahrul Rahmansyah; Billy Castyana (Indonesian Journal of Kinanthropology (IJOK), 2023)
Background: The development of technology is important for humans because it has various benefits to make it easier to do work, it also creates new habits that continue to develop, including in the world of education, the existence of the Blended Learning method encourages effective and efficient learning by combining digital media with traditional learning so as to make alternative methods in learning.. Methods: This research is a quantitative descriptive study conducted on high school students in the city of Semarang for Physical Education with a descriptive non-experimental research design using a survey method. The primary data source is the result of a survey of 683 respondents and direct field observations. The data is then processed and analyzed in Microsoft Excel and presented in the form of a percentage chart. Results: The results of this study are that there is effectiveness in the use of the Blended Learning method in Physical Education, namely Blended Learning type 2 is effectively used in Invasion Games material (68.77%) and Athletics (67.31%) while in Net-Games material (68 .38%) effectively using the Blended Learning type 3 method. Conclusions: The conclusion in this study is that there is an effectiveness of using Blended Learning in high school physical education material about Invasion Games, Net-Games and Athletics with different types of Blended Learning. This research is only focused on the high school level and there is a need for further research for other levels of education.